Refining Ranked Retrieval Results for Legal Discovery Search Through Supervised Rank Aggregation - Almquist, Brian; Srinivasan, Padmini (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
We propose and evaluate a data mining system that uses a set of document features describing each document in the context of partially evaluated ranked results. We find our system to be competitive with existing metasearch ranking strategies for prioritizing the review of evidence for legal relevance. Nous proposons et évaluons un système de fouille de données basé sur une série de descripteurs de documents décrivant chaque document dans un contexte d’évaluation partielle des résultats classés. Nous concluons que notre système est concurrentiel par rapport aux stratégies existantes de classement des métarecherches pour la priorisation de l’examen des preuves en matière de pertinence juridique.